The Succession of the Gut Microbiota in Insects: A Dynamic Alteration of the Gut Microbiota During the Whole Life Cycle of Honey Bees (Apis cerana) - Zhi-Xiang Dong; Yi-Fei Chen; Huan-Yuan Li; Qi-He Tang; Jun Guo (Frontiers in Microbiology, 2021)
The Asian honey bee Apis cerana is a valuable biological resource insect that plays an important role in the ecological environment and agricultural economy. The composition of the gut microbiota has a great influence on the health and development of the host. However, studies on the insect gut microbiota are rarely reported, especially studies on the dynamic succession of the insect gut microbiota. Therefore, this study used high-throughput sequencing technology to sequence the gut microbiota of A. cerana at different developmental stages (0 days post emergence (0 dpe), 1 dpe, 3 dpe, 7 dpe, 12 dpe, 19 dpe, 25 dpe, 30 dpe, and 35 dpe). The results of this study indicated that the diversity of the gut microbiota varied significantly at different developmental stages (ACE, P = 0.045; Chao1, P = 0.031; Shannon, P = 0.0019; Simpson, P = 0.041). In addition, at the phylum and genus taxonomic levels, the dominant constituents in the gut microbiota changed significantly at different developmental stages. Our results also suggest that environmental exposure in the early stages of development has the greatest impact on the gut microbiota. The results of this study reveal the general rule of gut microbiota succession in the A. cerana life cycle. This study not only deepens our understanding of the colonization pattern of the gut microbiota in workers but also provides more comprehensive information for exploring the colonization of the gut microbiota in insects and other animals.